2012
DOI: 10.1093/cid/cis976
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mefloquine Intermittent Preventive Treatment in Pregnancy Against Schistosoma haematobium Infection in Gabon: A Nested Randomized Controlled Assessor-Blinded Clinical Trial

Abstract: NCT01132248; ATMR2010020001429343.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…The activity of mefloquine on all the schistosome stages, the multiplicity of targets and the various damages observed on treated worms suggest a complex mode of action, involving both a heme-dependent pathway and a heme-independent mechanism [57][58][91][92]. In summary, the natural-derived drug mefloquine shows antischistosomal activity in animal models [57,[91][92] and clinical trials [93,94], which calls for further investigations in the treatment and control of schistosomiasis.…”
Section: Future Science Groupmentioning
confidence: 97%
“…The activity of mefloquine on all the schistosome stages, the multiplicity of targets and the various damages observed on treated worms suggest a complex mode of action, involving both a heme-dependent pathway and a heme-independent mechanism [57][58][91][92]. In summary, the natural-derived drug mefloquine shows antischistosomal activity in animal models [57,[91][92] and clinical trials [93,94], which calls for further investigations in the treatment and control of schistosomiasis.…”
Section: Future Science Groupmentioning
confidence: 97%
“…In an exploratory trial in Côte d'Ivoire, a mefloquine-artesunate combination showed a moderate cure rate (61%) and high egg reduction rate (96%) in school-aged children infected with S. haematobium [19]. Recently, mefloquine, used as intermittent preventive therapy against malaria in pregnancy (IPT p ), showed high egg reduction rates in women with a concomitant S. haematobium infection [20]. However, combination therapy with mefloquine and praziquantel, which showed high worm burden reductions in laboratory animals [21], has not yet been studied in Schistosoma -infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the excellent antischistosomal activity of mefloquine (MQ, Figure 1) was demonstrated in S. haematobium , S. japonicum and S. mansoni rodent models [8]. The promising results obtained with MQ in laboratory studies were followed up in clinical trials in the past years [9, 10]. Over the last decade, there has been increasing interest in metal-based drugs and numerous metal complexes have been synthesized and evaluated as antimalarial agents [11].…”
Section: Introductionmentioning
confidence: 99%